THE INTELLECTUAL LABOR OF DIGITAL BLACK FEMINIST ENCLAVES IN HASHTAG CONSTRUCTION, RECEPTION, AND STRATIFICATION ONLINE - Hardy, Alisa (AoIR Selected Papers of Internet Research, 2023)
While existing research has examined counterpublics in hashtag activism, little attention is given to digital enclaves that emerge when mainstream media disregards the voices of these communities. This paper helps us understand the process of hashtag activism that derives from the intellectual labor of digital enclaves. I examine the digital Black feminist enclave that emerged through the Black online magazine, Ebony, mobilizing #MuteRKelly on Twitter. #MuteRKelly brings attention to musical artist’s, Robert Sylvester Kelly, sexual exploitation of Black women and girls. I combined digital Black feminist theory with critical technocultural discourse analysis to demonstrate how this Black feminist enclave maximized Ebony’s interface to defy ideologies of capitalism, racism, colonialism, and sexism that underpin the music industry’s public allegiance to Black women’s exploitation on and offline. This digital Black feminist enclave solidified in the rhetorical and technical demand of #MuteRKelly, for (1) the music industry to dispatch all financial, commercial, and social engagements with Kelly and resist negative ideologies of Black women inscribed in his musical lineage, (2) for mainstream media to eradicate discourse that romanticizes domestic violence from celebrity Black men, and (3) for survivors’ to take space in the digital sphere to assemble a grapevine rhetorically committed to advocacy aimed at legal justice and increased protection for Black women and girls. It is important for scholars to trace the lineage of internet practices that traverse to hashtag activism and for us to look at the digital enclaves that produce these practices.